PROSPEK HOME INDUSTRI EKSTRAK JAHE MERAH DESA TRIYOSO KECAMATAN BELITANG (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
In the Home industry Venture East OKU extract red Ginger is one form of business in an effort to increase profits, where red ginger extract products are ready to be consumed will be marketed directly to the consumer, so it can know the prospect of Red ginger as the raw material manufacture of ginger extracts in the village of Triyoso. The total of the average production costs incurred by the respondent in an attempt to extract red ginger home industry in the village of Triyoso that is Rp. 1.624.872,-process. Production of the first week of as much as 125 toplesproses with the selling price of Rp. 20.000,-the jar then gained acceptance of Rp. 2,500,000,-process. The production of the second week of production that generated as many as 125 toplesproses and gain acceptance of Rp. 2,500,000-process. On the third week of the production processes generate 163 toplesproses, then acceptance gained Rp. 3.260.000/process. While in week four of the production process that produced as many as 150 toplesproses, then gained acceptance of Rp. 3,000,000,-process. Then the average production, prices and admission per production process is 141 jar with the selling price of Rp. Rp. 20.000,-the jar so that the receipt obtained amounted to Rp. 2.815.000,-process. Analysis of the average RC obtained at one of 1.73, this means that each Rp. 1.0-capital stock is used will gain acceptance of Rp. 1.73, RC values greater than 1 then the venture profitable. Red ginger extract agribusiness effort deserves to be developed because it is a test of BC retrieved amounted to 0.73. This means that any production cost incurred amounting to Rp. 1,-then it will earn profits of Rp. 0.73.